Analysis of Senior High School Students’ Writing Errors through Surface Strategy Taxonomy - Tokan, Monika Ethiafani; Sari, Valentina Dyah Arum (Formosa Journal of Multidisciplinary Research, 2024)
The Indonesian curriculum expects high school students to be able to write formal invitations for school or work events. These invitations should be well-structured, use appropriate language, and follow proper social etiquette, all according to the specific situation. In the early observations and interviews suggested students struggled with writing. Thus, this study aimed to analyze the types of errors found in the writing of senior high school students. This research was conducted by using descriptive qualitative method. The subjects of this study were 14 eleventh grade students in one state of the senior high schools in Sleman, Special Region of Yogyakarta. The results showed that there were two types of errors found in the students' writing based on the Taxonomy of Surface Strategies called: Omission 12 times (75%), Misinformation 4 times (25%).